2020
DOI: 10.2478/prolas-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Physiological Benefits of Short-Chain Fatty Acids from Cereal Grain Fibre Fermentation and Metabolic Syndrome

Abstract: Currently, intervention studies in humans have demonstrated that dietary fibre and whole grain consumption increase gut bacterial diversity. However, low-fibre intake drives depletion of the human gastrointestinal microbiota and indirectly stimulates metabolic abnormalities linked to metabolic syndrome insulin-resistance and abdominal obesity. The aim of the current paper was to summarise current evidence for the effect of consumption of cereal fibres on gut microbiota composition and their metabolites. By inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…and Bifidobacterium appeared to be the predominant orders in the fecal inoculum (Table 5), belonging to the Firmicutes and Actinobacteria phyla, respectively. Firmicutes spore-forming bacteria typically account for 64-78% of Western human microbiota [60]. Although the Actinobacteria phylum is proportionally less abundant [59], it has been found that subjects adopting a Mediterranean diet had a higher abundance of Bifidobacterium [61].…”
Section: Colonic Bioaccessibility Of Metabolites Formed By Microbial ...mentioning
confidence: 99%
“…and Bifidobacterium appeared to be the predominant orders in the fecal inoculum (Table 5), belonging to the Firmicutes and Actinobacteria phyla, respectively. Firmicutes spore-forming bacteria typically account for 64-78% of Western human microbiota [60]. Although the Actinobacteria phylum is proportionally less abundant [59], it has been found that subjects adopting a Mediterranean diet had a higher abundance of Bifidobacterium [61].…”
Section: Colonic Bioaccessibility Of Metabolites Formed By Microbial ...mentioning
confidence: 99%